Honeybee Nests Composition, Structure, Function - Hepburn, H.R.; Pirk, C.W.W.; Duangphakdee, O.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This work, a sequel to Honeybees and Wax published nearly 30 years ago, starts with a brief introduction and discussion of nesting sites, their spaces and densities, self-organization of nest contents, and interspecific utilization of beeswax. The following chapters cover communication by vibrations and scents and wax secretion, and discuss the queen in relation to the combs. Discussions on completed nests include the significance of brood, the roles of pollen and nectar flow, and comb-building, and are followed by a triad of related chapters on the construction of cells and combs and their energetic costs. An in-depth examination of the conversion of wax scales into combs, the material properties of scale and comb waxes, and the wax gland complex are presented. The next chapters are devoted to a comprehensive analysis of the literature on the chemistry and synthesis of beeswax, and, finally, the material properties of honeybee silk are highlighted.
General Introduction -- Nesting: Sites, Space and Density in Comb-building -- Self-organization of Nest Contents -- Intraspecific and Interspecific Comb-building -- Communication by Vibrations and Scents in Comb -- Wax Secretion, Comb Construction and the Queen -- The Significance of Brood -- The Role of Pollen in Honeybee Colonies -- Nectar Flows and Comb-building -- Construction of Combs -- Energetics of Honey/Beeswax Conversion -- Construction of Cells -- Conversion of Wax Scales into Comb Wax -- Material Properties of Scale and Comb Wax -- The Wax Gland Complex -- The Chemistry of Beeswax -- Synthesis of Beeswax -- Material Properties of Honeybee Silk.
Keywords: Life sciences; Bioorganic chemistry; Entomology; Biophysics; Biological physics; Biomaterials; Life Sciences; Entomology; Biophysics and Biological Physics; Biomaterials; Bioorganic Chemistry; Electronic books